PERTANGGUNGJAWABAN HUKUM DALAM PENEMBAKAN PESAWAT UDARA SIPIL DITINJAU DARI ASPEK HUKUM INTERNASIONAL - Widarto, Bambang (Jurnal Yuridis, 2014)
In the fact there was a shooting of a civilian by a military aircraft either with water-to-air missiles with aircraft or ground-to-air missiles. In this paper formulated problems: How the regulation of a country as contracting party of Chicago Convention respects for civil aviation safety and how the Chicago Convention regulate to refrain from using weapons against civil aircraft? The discussion also extends to how the conventions regulate respects and protection against civil aircraft in time of war according to the law of international armed conflict (Law of Armed Conflict); and how the provision of war crimes (war crimes) and crimes against humanity (crimes against humanity) are related to the shooting of civil aircraft in the Rome Statute of 1998?. Legal liability in accordance with the perpetrators of the events can be associated with the provisions of international law which can be found in Article 3 bis Chicago Convention of 1944, the Montreal Convention of 1971, the Beijing Convention of 2010, the Beijing Protocol of 2010, the provisions of Crimes against humanity in the Rome Statute of 1998, and in time of war (armed conflict) may be associated with the Geneva Convention of 1944, Protocol 1 and 2, 1977, and the war crimes defined in the article 8 of Rome statute 1998